Pengaruh Tata Kelola Perusahaan dan Struktur Kepemilikan Terhadap Persistensi Laba Perusahaan Properti di Masa Covid-19 - Resti Herawati; Siti Wahidatul Hasanah; Achmad Daffi Muzhaffar (Jurnal Publikasi Ilmu Manajemen, 2023)
Profit persistence refers to a stable and sustainable profit trend in the future. The purpose of this study is to analyze and test the effect of the composition of the board of commissioners, audit committee, and managerial ownership on the persistence of profits in property companies during the Covid-19 pandemic. The data analysis method used in this study is descriptive statistical analysis, and inferential statistical analysis using multiple regression to test the research hypothesis. The results showed that (1) the composition of the board of commissioners proved to have no significant effect on the persistence of earnings in LQ45 index property companies during the Covid-19 period. (2) The Audit Committee has been proven to have no significant effect on the persistence of earnings in LQ45 index property companies during the Covid-19 period. (3) Managerial Ownership has been shown to have no significant effect on the persistence of earnings in LQ45 index property companies during the Covid-19 period. Profit persistence is influenced by several factors, but one of them is corporate governance.